Digital transformation, artificial intelligence and society opportunities and challenges - Kumar, Sachin; Mirza, Amna; Verma, Ajit Kumar 1959- (Springer, 2024)
"This book examines the fundamental concepts and principles of digital transformation and AI, including their historical development, and underlying technologies, and analyzes the opportunities arising from digital transformation and AI in different sectors, such as healthcare, finance, education, transportation, and governance. It provides a comprehensive overview of digital transformation and AI technologies and their current state of implementation. It also explores the potential challenges and risks associated with digital transformation and AI, including ethical considerations, job displacement, privacy concerns, biases, impact on inequality, social interactions, and the overall well-being of individuals and communities. Additionally, the books provides and discusses policy and regulatory frameworks that can effectively address the opportunities and challenges posed by digital transformation and AI leading to responsible AI. It also delves into impact of automation on the job market and workforce. The book concludes by proposing potential strategies for navigating opportunities and challenges of digital transformation and AI integration. It emphasizes the need for interdisciplinary collaboration among stakeholders, including policymakers, industry leaders, academia, and civil society, to develop a comprehensive approach towards harnessing the full potential of digital transformation and AI and associated technologies. The book employs a multidisciplinary approach, drawing from various fields such as computer science, sociology, philosophy, political science, economics, law and governance. It combines theoretical analysis, empirical case studies, and expert perspectives to provide a holistic view of the subject matter. This book caters to a diverse audience, including students, researchers, academics, policymakers, industry professionals, and technology enthusiasts. [...]"